A new mechanism regulating microglial NLRP3 inflammasome: FMR1 mediates NLRP3 mRNA stability - Qian Deng; Qianqian Bai; Yang Yang; Wenchao Tang; Fangfei Liu; Shumin Zhang; Hao Wang; Zhehua Xing; Chi Zhang; Yanhui Yang; Qizhi Fu; Hua Fan (PLoS ONE, 2026)
Background The NLRP3 inflammasome drives chronic inflammation and contributes to the pathogenesis of multiple sclerosis (MS). This study aimed to elucidate a novel post-transcriptional regulatory mechanism controlling NLRP3 expression in microglia under lipopolysaccharide (LPS) stimulation. Methods The experimental autoimmune encephalomyelitis (EAE) mouse model of MS was established and divided into four groups: Sham, EAE, EAE + Lv-con (control lentivirus), and EAE + Lv-FMR1 (FMR1-overexpressing lentivirus). BV2 microglial cells were stimulated with LPS and adenosine triphosphate (ATP). mRNA and protein levels were assessed by qPCR, western blot, immunofluorescence, and immunohistochemistry. Caspase-1 activity and IL-1β/IL-18 levels were quantified using commercial assay kits. RNA-binding proteins (RBPs) interacting with NLRP3 mRNA were identified by RNA pull-down combined with mass spectrometry. NLRP3 mRNA stability was analyzed using Actinomycin D. Results NLRP3 inflammasome activation was confirmed in the spinal cords of EAE mice and in LPS/ATP-stimulated BV2 cells. Lentivirus-mediated overexpression of FMR1 in EAE mice attenuated microglial activation (reduced IBA-1) and decreased NLRP3 expression compared to the EAE + Lv-con control group. Immunohistochemistry confirmed reduced caspase-1 deposition in the EAE + Lv-FMR1 group. Mechanistically, FMR1 directly interacted with the 3’ untranslated region (3’UTR) of NLRP3 mRNA in LPS/ATP-treated BV2 cells, leading to mRNA destabilization and consequent suppression of NLRP3 protein expression. Functionally, FMR1 inhibited NLRP3 inflammasome activation by downregulating NLRP3. Conclusion FMR1 suppresses NLRP3 inflammasome activation in both EAE mice and microglial cell models by destabilizing NLRP3 mRNA. This suggests that FMR1 possesses therapeutic potential for MS by dually regulating neuroinflammation and NLRP3-driven pathology.